Analisis Badan Pengelolaan Keuangan Daerah Dalam Pengamanan Aset Tetap Kota Subussalam - Yuli Ekawati; Laylan Syafina; Yenni Samri Juliati Nasution (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2023)
This research aims to analyze the role of the Regional Financial Management Agency (BPKD) in securing fixed assets in Subulussalam City. Fixed assets play an important role in the financial structure of local governments, including land, buildings, infrastructure and other facilities used for public service activities. Effective management and security of these assets is essential to ensure efficient utilization of local financial resources. This study examines BPKD's responsibilities in procurement, inventory, assessment and maintenance of assets. The benefits of effective asset security are also discussed, the challenges faced by the BPKD in securing fixed assets, and strategies to increase asset security. The findings contribute to improving financial management practices and optimizing asset utilization in Subulussalam City. This research was conducted at the Subulussalam City BPKD Regional Financial Management Agency Office. This study used descriptive analysis method, and made direct observations by visiting the Subulussalam City BPKD, as well as conducting interviews with related parties. Data collection techniques include observation, interviews, writing and reading. The data analysis process is then carried out by collecting, reducing, presenting and drawing conclusions from or confirming the data. The results of this study indicate that the BPKD is a part that coordinates and is used as a coordinator for managing regional assets that are not yet good at carrying out their duties and functions.